DIGITALISASI REGISTER PELAPORAN BABINSA: TRANSFORMASI WACANA FORENSIK DALAM MONITORING PEMBANGUNAN DESA BANDAR DOLOK - Sarma panggabean; Febrika Dwi Lestari; Samuel B.T Simorangkir (Merwinspy Publisher, 2026)
The digitalization of reporting systems is essential for ensuring transparency in rural governance; however, data validity remains a persistent challenge in manual reporting practices. This community service program aimed to transform the Babinsa reporting system in Bandar Dolok Village from conventional documentation into a forensic discourse–based digital reporting system. The program employed a Community-Based Action Research (CBAR) approach over three months, resulting in the implementation of the Bandar Dolok Smart-Monitoring application equipped with metadata encryption, geotagging, and automated timestamps. The implementation significantly improved data integrity, with spatial accuracy increasing by 95% and narrative objectivity improving by 91%. Reporting practices shifted from subjective descriptions to verifiable digital evidence with audit value. Beyond accelerating information flow, the system enhances transparency and accountability in village development monitoring. The program concludes that forensic-based digitalization can establish a transparent, accountable, and tamper-resistant development monitoring system.